A utilização da robótica educacional com a plataforma Arduino : uma contribuição para o ensino de Física - Luciano, Ana Paula Giacomassi (2014)
One of the problems encountered in research about teaching of physics in the country is the emotional distancing of students concerning curricular component of physics, which directly influences on learning this component. In this context, educational robotics presents as an option for educational-learning resource to alleviate this problem, as it has a strong motivational impact. Educational robotics allows learners to develop skills such as logical reasoning and creativity, based on the use of technology to illustrate current applications of physical content. Thus, our research aimed to investigate, from the analysis of teaching physical concept of torque in that educational robotics can contribute to an affective approximation of students with the discipline of physics, and identify the extent to which this approach favors learning of physics concepts. To achieve this goal, the following guidelines and proposals constructionist Papert, developed an instructional sequence in order to organize workshops that could prepare students to build a robot that perceives changes in ambient light. We chose this research to develop a robotic device that make use of low cost materials, because this way is not limited to their impact on application. So we used the Arduino platform for the development of this device, as well as it is a free software making its low cost , yet allows great freedom in hardware structures allowing commands and actions that provide a wide range of diversity issues to address. Together with the assumptions of constructionism, the Arduino can greatly facilitate the learning of physics concepts. The subjects involved in this study were six students of the second year of high school of college public schools belonging to the regional center of Maringá. The data collection performed in two stages, one semi-structured interview that preceded the series of workshops and other project after conducting these workshops proposals. The data analysis follows the technique of content analysis proposed by Bardin. During the development of activities took advantage to discuss and address various concepts underlying physics, such as electrical circuits, and mechanical phenomena related issue addressed in this study, the concept of torque. With the use of educational robotics as a teaching resource, it could verify that it enabled an affective approximation of students with physics curriculum component. The speeches collected in the interviews point to the difficulty in correlating student knowledge of physical concepts to everyday applications due to the overhead of emphasis used mathematical description of contents. We can notice through the narratives of the students involved in the research that the use of educational robotics, using the Arduino platform, favored to an affective approximation to the physics curriculum component, producing positive effects in relation to the learning of concepts involved with even if the concept studied torque.